﻿International Conference on Aquatic Invasive Species – ICAIS returned to Europe after 15 years - Hugo Verreycken; Frank P. L. Collas; Neil E. Coughlan (Aquatic Invasions)
The 22nd International Conference on Aquatic Invasive Species (ICAIS) was held as a hybrid event in Oostende, Belgium from 18–22 April 2022. The conference addressed the theme of “Global Climate Change Amplifies Aquatic Invasive Species Impacts” and aimed to expand knowledge on the latest science and policy, inspire cooperation and collaboration on research and management projects at a global scale. Seven renowned international scientists provided keynote presentations on perspectives of climate change within their respective areas of expertise. This special issue of Aquatic Invasions presents nine academic papers addressing a range of aquatic invasive species issues including predation, life history dynamics, ecosystem impacts, and physiological tolerances. The papers highlight the need for regional, national, and international cooperation, collaboration on research and management projects, and targeted, specific, and actionable outreach to combat the growing threat posed by aquatic invasive species.